2020
DOI: 10.30935/cedtech/9341
|View full text |Cite
|
Sign up to set email alerts
|

Examination of University Students' Attitudes towards E-learning during the COVID-19 Pandemic Process and the Relationship of Digital Citizenship

Abstract: The COVID-19 pandemic has had an impact on people's social interaction and has brought changes on education, environment and economy. COVID-19, which affects every aspect of life, has produced results that require re-evaluating the perspective on education. Distance learning, digital learning, e-learning has reshaped education in many ways. There can be a chance of the pandemic in the digital age to turn into an advantage for the education sector. In this period, it can be said that those who have high interes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 26 publications
1
50
0
1
Order By: Relevance
“…The focus of most articles is distance learning or the change from face-to-face to distance learning. There are several perspectives, like mobile learning methodology [34] and gamification [35], for a specific subject [36,37]; for a specific group of students, such as international mobility students [38] or first-year students [39]; concerned with the quality of educational process on online platforms [40], the level of communication of social responsibility by higher education institutions [41] or technical conditions of distance learning [42]; adaptation of the learning process [43], concern about connecting to the digital world [44][45][46]; the influence of some factors on students' acceptance of shifting education to distance learning [47], Evaluation of the Emotional and Cognitive Regulation [48], comparison of face-to-face classes with distance learning [49] by the student's perspective [50,51], teacher's perspective [43,52], organization [53], or various actors [54].…”
Section: Systematic Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The focus of most articles is distance learning or the change from face-to-face to distance learning. There are several perspectives, like mobile learning methodology [34] and gamification [35], for a specific subject [36,37]; for a specific group of students, such as international mobility students [38] or first-year students [39]; concerned with the quality of educational process on online platforms [40], the level of communication of social responsibility by higher education institutions [41] or technical conditions of distance learning [42]; adaptation of the learning process [43], concern about connecting to the digital world [44][45][46]; the influence of some factors on students' acceptance of shifting education to distance learning [47], Evaluation of the Emotional and Cognitive Regulation [48], comparison of face-to-face classes with distance learning [49] by the student's perspective [50,51], teacher's perspective [43,52], organization [53], or various actors [54].…”
Section: Systematic Literature Reviewmentioning
confidence: 99%
“…the sample size varies widely: from 100 or less [38,39,51], 250 or less [37,40,45,46,49,50,55], less than 1000 students [42,44,54], or more than 1000 [47,48]. Two studies use the General Extended Technology Acceptance Model for E-Learning (GETAMEL) [39,47], one study uses the Digital Citizenship Behavior Scale (DCB) [45] and another uses the Cognitive Emotion Regulation Questionnaire (CERQ) [48]. One of the studies uses three surveys: at the beginning, in the middle, and at the end of the semester [35], while another compares student surveys in the semester prior to the pandemic with the surveys of students who participated in the course during the pandemic [49].…”
Section: Systematic Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it has been observed that the negative anxiety of students due to the pandemic is reflected in their e-learning processes. However, overall results show that digital citizenship behavior digital learning process could be a positive response to COVID-19 closure period (Akcil & Bastas, 2021).…”
Section: Introduce the Problemmentioning
confidence: 86%
“…Due to the Covid-19 epidemic, there is a compulsory transition of schools to distance education throughout the world, and it is stated that the participation in the lessons is quite high as a result of the virtual adaptation of technology in the higher education institution in Bangalore and as a result of the students enjoying these experiences (Shenoy et al, 2020 ). In their work, Akcil and Bastas ( 2020 ) point out the importance of digital citizenship, with the transition from face-to-face education to online education during the Covid-19 pandemic process. In their studies with university students, they concluded that the relationship between digital citizenship behaviors and e-learning attitudes, which are effective in learning willingness in positive way.…”
Section: Introductionmentioning
confidence: 99%